Formate oxidation in the intestinal mucus layer enhances fitness of Salmonella enterica serovar Typhimurium - Maria G. Winter; Elizabeth R. Hughes; Matthew K. Muramatsu; Angel G. Jimenez; Rachael B. Chanin; Luisella Spiga; Caroline C. Gillis; Michael McClelland; Helene Andrews-Polymenis; Sebastian E. Winter (mBio, 2023)
ABSTRACT Salmonella enterica serovar Typhimurium induces intestinal inflammation to create a niche that fosters the outgrowth of the pathogen over the gut microbiota. Under inflammatory conditions, Salmonella utilizes terminal electron acceptors generated as byproducts of intestinal inflammation to generate cellular energy through respiration. However, the electron donating reactions in these electron transport chains are poorly understood. Here, we investigated how formate utilization through the respiratory formate dehydrogenase-N (FdnGHI) and formate dehydrogenase-O (FdoGHI) contribute to gut colonization of Salmonella. Both enzymes fulfilled redundant roles in enhancing fitness in a mouse model of Salmonella-induced colitis, and coupled to tetrathionate, nitrate, and oxygen respiration. The formic acid utilized by Salmonella during infection was generated by its own pyruvate-formate lyase as well as the gut microbiota. Transcription of formate dehydrogenases and pyruvate-formate lyase was significantly higher in bacteria residing in the mucus layer compared to the lumen. Furthermore, formate utilization conferred a more pronounced fitness advantage in the mucus, indicating that formate production and degradation occurred predominantly in the mucus layer. Our results provide new insights into how Salmonella adapts its energy metabolism to the local microenvironment in the gut. IMPORTANCE Bacterial pathogens must not only evade immune responses but also adapt their metabolism to successfully colonize their host. The microenvironments encountered by enteric pathogens differ based on anatomical location, such as small versus large intestine, spatial stratification by host factors, such as mucus layer and antimicrobial peptides, and distinct commensal microbial communities that inhabit these microenvironments. Our understanding of how Salmonella populations adapt its metabolism to different environments in the gut is incomplete. In the current study, we discovered that Salmonella utilizes formate as an electron donor to support respiration, and that formate oxidation predominantly occurs in the mucus layer. Our experiments suggest that spatially distinct Salmonella populations in the mucus layer and the lumen differ in their energy metabolism. Our findings enhance our understanding of the spatial nature of microbial metabolism and may have implications for other enteric pathogens as well as commensal host-associated microbial communities.